THE INFLUENCE OF BRAND IMAGE AND BRAND AWARENESS ON BRAND LOYALTY WITH BRAND TRUST AS MEDIATION OF BREADTALK (STUDY ON CINERE MALL BREADTALK CONSUMERS) - Rosalina Rosalina; Lenny Christina Nawangsari; Kusumo Bintoro (Sean Institute, 2023)
This study aims to determine the effect of brand image and brand awareness on brand loyalty and brand trust for mediation on BreadTalk. The type of research was survey research and the sampling method used questionnaires. The population in the research is BreadTalk consumers at Mall Cinere. The sampling technique was carried out by purposive sampling and a sample of 140 respondents was obtained. The results showed that brand image and brand awareness affected brand trust, while brand image and brand awareness affected brand loyalty, and brand trust affected brand loyalty. So, brand trust mediated the influence between brand image and brand loyalty and brand trust mediated the influence between brand awareness and brand loyalty.